CHARACTERISTICS OF THE COMPOSITION OF FATTY ACIDS IN PLASMA LIPIDS IN SUFFERING FROM INFILTRATIVE PULMONARY TUBERCULOSIS - Пикас, Ольга (Modern engineering and innovative technologies, 2022)
Purpose - the study was aimed at studying and evaluating fatty-acid composition of plasma lipids in suffering from infiltrative pulmonary tuberculosis.Methods. The fatty-acid composition of blood was studied by biochemical method on the gas-liquid chroma